Moderating roles of gender expression and social desirability in the link between status perception and assertive behaviour - Etumudor , Glory A.; Ndukaihe, Izuchukwu L. G (Journal of Psychology and Allied Disciplines, 2024)
The study was determined to look at the moderating roles of gender expression and social desirability in the link between status perception and assertive behaviour. The techniques used to select participants was targeted sampling techniques. Participants comprise 329 students both postgraduates and 400-level undergraduates from a federal university in Southeast, Nigeria. Questionnairescopies were used to collect data from participants. The research adopted a cross-sectional survey research design. Pearson product-moment correlations and regression analysis using the Hayes Process Macro were used to test the hypotheses. The results of the study indicate that there is no association between status perception and assertive behaviour. There is a significant association between gender expression and assertive behaviour, social desirability is significantly associated with assertive behaviour. Gender expression did not moderate the association between status perception and assertive behaviour, but, social desirability negativelymoderated the association between status perception and assertive behaviour. This result indicates that the interaction between high social desirability and low-status perception leads to an increase in assertive behavior and vice versa. Despite status perception does not significantly influence assertive behaviour, status events, like actions, communications, and associations that lead to increases and decreases in respect, admiration, reputation, prestige, deference, and influence are evaluated by our assertiveness.This is because one’s status can affect our social interaction, influence our social circle, and interest in society.